2020
DOI: 10.1177/0145561320933965
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Staging in the Treatment of Congenital Cholesteatoma in Children

Abstract: Objectives: To analyze the clinical characteristics of congenital cholesteatoma (CC), to explore the risk factors related to recurrence of the disease, and to clarify the importance of staging for treatment. Methods: A total of 87 patients were followed up for more than 5 years, who had undergone surgical procedures for CC from September 2010 to January 2017 in Beijing Children’s Hospital, Capital Medical University. Patients with CC were identified in accordance with the following Levenson’s criteria. The cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…The mean age of the included patients was 7.91 ± 3.11 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years. There were 8 and 3 cases of the left and right ear, respectively.…”
Section: Preoperative Examination Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the included patients was 7.91 ± 3.11 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years. There were 8 and 3 cases of the left and right ear, respectively.…”
Section: Preoperative Examination Resultsmentioning
confidence: 99%
“…Therefore, early CMEC detection and treatment are crucial for avoiding the occurrence of serious complications Currently, surgical treatment remains the only treatment for CMEC. [9] Its main objectives are to completely remove lesions, prevent recurrence, and preserve or rebuild hearing. For patients with CMEC, the classical surgical methods include modified radical mastoidectomy and tympanoplasty based on the lesion scope.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the recurrence rate of CMEC in children is 10.5%-45% [11,12]. At present most reports on CMEC are small-sample reports [7,11,[13][14][15][16], so there is no data to prove that otoendoscope can reduce the recurrence rate of CMEC.…”
Section: Discussionmentioning
confidence: 99%
“…Istotną rolę odgrywa wczesna diagnostyka perlaka, ponieważ wczesne wykrycie perlaka umożliwia wykonanie małoinwazyjnego zabiegu, co wpływa na zmniejszenie częstości powikłań i nawrotów [22,23]. Z kolei odpowiednio wczesne usunięcie zmian pozwala w większości przypadków na zachowanie prawidłowego słuchu i uniknięcie niebezpiecznych powikłań.…”
Section: Diagnostykaunclassified
“…W celu ułatwienia wykrycia i podjęcia odpowiednio wcześnie interwencji programy wczesnych badań przesiewowych mogą zalecać badania przesiewowe słuchu i tomografię komputerową. Wielu naukowców podkreśla także istotność rutynowego badania otoskopowego u lekarza POZ [34].…”
Section: Rola Badań Przesiewowychunclassified